Semantic Changes in GEN-Z Vocabulary: A Comparative Study of TikTok Language Use - M Ravly Pasya; Nailah Inaya Harahap; Nursetia Manalu; Rachel Angela Rosana Hutauruk; Meisuri Meisuri (CV. Rayyan Dwi Bharata, 2025)
This qualitative descriptive study investigates the rapid process of semantic change (meaning change) within Generation Z's vocabulary, specifically driven by the social environment of the TikTok platform. The research was designed to systematically compare a word’s original, established meaning with its new digital use, addressing a key gap in current studies. Utilizing a purposive sample of public TikTok comments, the research applied a descriptive review, comparing the dictionary meanings of key lexical items (e.g., slay, cap, rizz, glow up) with their contextual usage to categorize the change based on established linguistic mechanisms. The results clearly show that Gen Z vocabulary is changing significantly. The review confirmed four primary categories of change: Broadening (expansion of meaning, e.g., Slay and Glow Up), Narrowing (specialization, e.g., Rizz), Amelioration (positive or lighter shift, e.g., Cap and Clingy), and Metaphorical Extension (shift to figurative use, e.g., Peak). This research concludes that TikTok acts like a powerful engine for language evolution, accelerating the diffusion of these semantic change. This speed is driven by Gen Z's functional need for words that are highly expressive, efficient, and clearly mark their social identity online.